Assessing medication adherence and their associated factors amongst type-2 diabetes mellitus patients of Jazan Province, Saudi Arabia: A single-center, cross-sectional study. - Amani Khardali; Nabeel Kashan Syed; Saad S. Alqahtani; Marwa Qadri; Abdulkarim M. Meraya; Norah Rajeh; Fatimah Aqeely; Sedan Alrajhi; Amnah Zanoom; Shahd Gunfuthi; Wahhaj Basudan; Thana K. Hakami; et al. (Elsevier, 2024)
Background: The prevalence of type 2 diabetes mellitus (T2DM) globally is reaching epidemic proportions. By 2035, it is projected to increase to 417 million, which is of significant concern as T2DM represents the most oversized budget item in many healthcare systems, primarily due to the high rates of morbidity and mortality associated with the disease. The worldwide cost burden of T2DM has been inexorably growing. A key contributor to the remarkably high morbidity and mortality rates is poor glycemic control potentially associated with medication non-adherence. Aim: The present research's main objective included assessing medication adherence among patients with T2DM in a single center in Jazan Province. Methods: Three hundred nine patients with T2DM participated in a cross-sectional survey over three months (September to November 2022). The study participants comprised 50.8 % (females) and 49.2 % (males), with a mean age of 44.12 years (SD ± 12.70). A 31-item self-report questionnaire was used for data collection. Results: Sixty-six percent of the sample were found to be adherent to their T2DM therapy. A positive association was noticed between the GMAS score and the participant's age (r = 0.24; p < 0.01). The participants' medication adherence was significantly associated with having age above 50 years (χ2 = 13.62; p = 0.001), residing in urban localities (χ2 = 21.37; p < 0.001), being married (χ2 = 12.80; p = 0.002), having glycated hemoglobin level more than 8 % (χ2 = 6.99; p = 0.03) and taking between one to three medications per day (χ2 = 17.63; p < 0.001). Conclusion: The majority of T2DM patients in the present study were found adherent to their anti-diabetic medications, particularly older patients. Future studies should focus on exploring the reasons for the reported high adherence among older patients and non-adherence among younger patients, as this could facilitate the development of a strategy to enhance adherence.